THE REPRESENTATION OF PEACE VALUES IN THE ELT TEXTBOOK FOR SENIOR HIGH SCHOOL STUDENTS - Nisa, Jasmine Choirun; Suharjito, Bambang; Fitriani, Ika (ELLTER Journal, 2025)
In today’s era, acts of violence often transpire among senior high school students. An effective way to prevent this issue is by integrating peace values into the educational field and strengthening the role of textbooks as a medium to present universal values. In other words, the use of textbooks has the potential to promote peace values through textbook artifacts. Due to this, the current study aimed to investigate the representation of peace values in the ELT textbook entitled ‘Bahasa Inggris English for Change’, which serves as the learning medium for eleventh-grade senior high school students. This study is a descriptive qualitative design using critical discourse analysis and conducted in the Indonesian EFL context. A document analysis process was used to collect the data, which was analyzed using the Multimodality framework of Kress & Leeuwen. The findings show that two pictures and four photographs with the verbal texts represented peace with nature, and two pictures with the verbal texts represented inner peace. In line with this, the findings are beneficial for increasing understanding about the way to foster inner peace and peace with nature for the present and future generations.